Otto of the Silver Hand - Pyle, Howard 1853-1911 (Charles Scribner's, 1957)
The gentle son of a medieval German robber baron, raised in the calm and thoughtful quiet of a monastery, returns to his father's castle and, despite great suffering and blood-feuds, grows to honor and manhood.